Designed for Post-Growth: "Alternative Economies" between Micro- and Macro-Analyses - Haase, Michaela; Becker, Ingrid; Pick, Doréen (Marketing as Provisioning Technology: Integrating Perspectives on Solutions for Sustainability, Prosperity, and Social Justice: Proceedings of the 40th Annual Macromarketing Conference, 2015)

The Relevance of Male Breadwinner Ideology for the Analysis and Design of Marketing Systems - Haase, Michaela; Becker, Ingrid; Nill, Alexander; Shultz II, Clifford J.; Gentry, James W. (Proceedings of the 38th Annual Macromarketing Conference, 2013)
This paper continues and extends available work in macromarketing on the male breadwinner ideology (Nill and Shultz 2010). “Male breadwinning” designates the effects of shared and overlapping ideologies and thus also patterns of marketing systems. Like institutions, ideologies are both restrictions and enabler for market processes. Ideologies influence the economic organization and thus type and number of relationships in marketing systems. Our paper wants to contribute to the development of measures which can inform the private as well as public decision-making units about the ideologies available in actual as well as potential marketing systems and the influence they might have on the demand for particular offerings. Based on a qualitative pre-study, the paper develops a Male Breadwinning Model and conducts a vignette analysis in Southern Germany. First results of the vignette study are included.